Uterine involvement in epithelial ovarian cancer and its risk factors - Narges Zamani; Azam Sadat Mousavi; Setare Akhavan; Shahrzad Sheikhhasani; Somayeh Nikfar; Elham Feizabad; Elahe Rezayof; Mitra Modares Gilani (BMC, 2021)
Abstract Background Epithelial ovarian cancer (EOC) is an extremely aggressive and lethal carcinoma. Specific data that identify high-risk groups with uterine involvement are not available. Thus, this study aimed to evaluate a gross number of women with EOC to obtain the frequency of uterine involvement and its risk factors. Methods This retrospective observational study was conducted on 1900 histologically confirmed EOC women, diagnosed and treated in our tertiary hospital from March 2009 to September 2020. Data including their demographic, medical and pathological findings were collected. Results From 1900 histologically confirmed EOC women, 347 patients were eligible for participations. The mean age of study patients was 51.31 ± 11.37 years with the age range of 25 to 87 years. Uterine involvement was detected in 49.6% (173) of the patients either macroscopic (47.4%) or microscopic (52.6%) types. Uterine involvement was significantly associated with having AUB (P-value = 0.002), histological type of ovary tumor (P-value < 0.001), ovarian cancer stage (P-value < 0.001), and abnormal CA-125 concentration (P-value = 0.004). Compared to the other study patient, the patients with metastatic uterine involvement had significantly higher stage (p-value< 0.001), higher grade of ovary tumor (p-value = 0.008), serous histological type (p-value< 0.001), and a higher level of CA-125 concentration (p-value< 0.001). on the other hand, the patients with synchronous uterine cancer were significantly younger (p-value = 0.013), nulliparous (p-value< 0.001), suffered from AUB symptoms (p-value< 0.001) and had endometroid histological type (p-value = 0.010) of ovary cancer in comparison to other study patients. Conclusion Considering the high prevalence of uterine involvement in EOC patients, ultrasound evaluation and/or endometrium biopsy assessment should be done before planning any treatment.